Psychosocial impacts, perceived stress, and learning effects during the transition from preclinical to clinical dental education: Validation and translation of a questionnaire - Maryam Sadeghipour Roudsari; Mahshid Namdari; Hamed Mortazavi; Mahsa Malek-Mohammadi; Sajjad Tohidi (Wolters Kluwer Medknow Publications, 2022)
Background: During the first experiences of clinical treatment, dental students face various challenges. The purpose of the study is to standardize the questionnaire as a suitable tool for quantitative and qualitative evaluation of psychosocial impact, stress levels, and learning effect of dental students during the transition from preclinical to clinical education in Persian. Materials and Methods: In this cross-sectional study a questionnaire including three areas of psychosocial impact, perceived stress, and learning effect was systematically translated. In the group of experts, face validity was examined. Then, the content validity ratio (CVR) and the content validity index (CVI) were determined. The reliability of the questionnaire was determined by the test-retest method and the Cohen's Kappa coefficient. In a cross-sectional study, the psychosocial impact, stress levels, and learning effect of all students newly admitted to the endodontic, prosthetics, periodontics, and restorative dentistry departments of Shahid Beheshti Dental School (128 people) were measured. Mann-Whitney and Spearman-Rho were used for statistical analysis (P = 0.05). Results: During the CVR and CVI evaluation, 12 statements were removed from the questionnaire, and one statement was changed. All valid statements of the questionnaire were considered reliable. The initial questionnaire was finally developed in the form of 27 items. Interest in clinical treatment and collaboration between students and faculty had the greatest psychosocial effects. The highest level of stress among students was seen in the endodontic ward (mean = 3.8). The greatest effect of learning was seen in different sections in infection control (mean >4). Conclusion: This study provided a standardized tool in Persian to evaluate the psychosocial impacts, perceived stress, and learning effect of dental students during the transition to clinical education and focused on the first clinical treatment experiences. One important psychosocial factor was collegiality between teachers and students. The ability to communicate well with the patient is thought to reduce stress.